Perception of Montessori preschool teachers regarding literacy development through technology-supported play-based activities - Margaret F. Omidire; Shine Aung; Etinosa Izevbigie; Seboke P. Shai (Reading & Writing, 2025)
Background: As technology continues to evolve, educators and researchers are exploring innovative ways to harness the potential of technology to enhance literacy development for young learners. The Montessori approach to teaching and learning is an interactive approach that caters to diverse learning needs, as well as the individual learner’s interests.